Suporte social no trabalho, suporte organizacional e comprometimento organizacional: um estudo com professores da rede municipal de ensino - Campos, Simone Alves Pacheco de (2011)
This study was developed with the aim of identifying relationships between social support at work, organizational support and organizational commitment, considering the reality experienced by teachers of municipal schools. To this end, we carried out a descriptive survey research, quantitative and qualitative. First, the quantitative phase, with 336 teachers from the city, we used a structured questionnaire from three models: the Scale of Perceived Social Support at Work (GOMIDE JUNIOR, GUIMARÃES and DAMÁSIO, 2004; 2008), Scale Perceived Organizational Support (SIQUEIRA1995, 2008) and the Scale of Bases of Organizational Commitment, (MEDEIROS et al, 2005). After this, a qualitative step, through structured interviews with directors of six municipal schools. Regarding social support at work, the results signaled a similar perception among teachers and principals, indicating a greater presence of emotional social support and lower perceived instrumental support. With respect to organizational support, we can see that teachers and principals have different perceptions. While the teachers expressed a high perceived organizational support from schools, reports of the directors point to a lack of organizational support, since in their perception, there are only isolated organizational initiatives in order to provide welfare and job satisfaction. With respect to organizational commitment in relation to teachers, the results indicate a high normative commitment, through the enhancement of the Performance Based Requirement, and, for directors, a high affective commitment. Still, the results of this study indicated that both teachers and principals have a low appreciation of instrumental commitment. By establishing relationships between the constructs, the results indicated that social support at work, organizational support and organizational commitment are related. Considering the relationship between social support at work and organizational commitment, we observed high ratios exist between emotional support and the Affiliates and Affective bases, while, on the other hand, instrumental social support correlated weakly with all the bases of organizational commitment. In relation to organizational support, the results showed high correlations between this construct and strong bases Affiliate Obligation Stay and Affective. Finally, with respect to the relationship between social support at work and organizational support, it was observed that there were high associations between social support and emotional and instrumental perceptions of organizational support.